Purloined letters : cultural borrowing and Japanese crime literature, 1868-1937 - Silver, Mark (University of Hawaiʼi Press, 2008)
This engaging study of the detective story's arrival in Japan--and of the broader cross-cultural borrowing that accompanied it--argues for a reassessment of existing models of literary influence between "unequal" cultures. Because the detective story had no pre-existing native equivalent in Japan, the genre's formulaic structure acted as a distinctive cultural marker, making plain the process of its incorporation into late nineteenth- and early twentieth-century Japanese letters. Mark Silver tells the story of Japan's adoption of this new Western literary form at a time when the nation was also remaking itself in the image of the Western powers. His account calls into question conventional notions of cultural domination and resistance, demonstrating the variety of possible modes for cultural borrowing, the surprising vagaries of intercultural transfer, and the power of the local contexts in which "imitation" occurs. Purloined Letters considers a fascinating range of primary texts populated by wise judges, faceless corpses, wily confidence women, desperate blackmailers, a fetishist who secrets himself for days inside a leather armchair, and a host of other memorable figures. The work begins by analyzing Tokugawa courtroom narratives and early Meiji biographies of female criminals (dokufu-mono, or "poison-woman stories"), which dominated popular crime writing in Japan before the detective story's arrival. It then traces the mid-Meiji absorption of French, British, and American detective novels into Japanese literary culture through the quirky translations of muckraking journalist Kuroiwa Ruiko. Subsequent chapters take up a series of detective stories nostalgically set in the old city of Edo by Okamoto Kido (a Kabuki playwright inspired by Arthur Conan Doyle's Sherlock Holmes) and the erotic, grotesque, and macabre works of Edogawa Ranpo, whose pen-name punned on "Edgar Allan Poe